1992
DOI: 10.1046/j.1537-2995.1992.32292180138.x
|View full text |Cite
|
Sign up to set email alerts
|

Paired comparison of platelet concentrates prepared from platelet‐rich plasma and buffy coats using a new technique with111In and51Cr

Abstract: Two techniques for the preparation of platelet concentrate (PC), the standard platelet-rich plasma (PRP) and buffy coat (BC) methods, were compared in nine paired studies with regard to platelet harvest, white cell (WBC) contamination, and PC quality after 5 days of 22 degrees C storage. Platelet harvest using the BC method averaged approximately 56 percent of the whole blood level (6.2 x 10(10)/concentrate), which was less than the 76 percent achieved with the PRP-PC method (8.7 x 10(10)/concentrate). An addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 31 publications
4
34
1
Order By: Relevance
“…However, during the storage time of PC these differences diminished [12]. Thus, it is not surprising that no relevant differences could be found in clinical studies comparing in vivo recovery and survival of transfused PRP-PC and BC-PC after storage for 5 days [17]. Investigations with fresh PC probably might show differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the storage time of PC these differences diminished [12]. Thus, it is not surprising that no relevant differences could be found in clinical studies comparing in vivo recovery and survival of transfused PRP-PC and BC-PC after storage for 5 days [17]. Investigations with fresh PC probably might show differences.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have shown no difference in the quality of these plt concentrates when they are stored for up to 7 days. 3,4 However, there is emerging evidence that, when plts are stored for extended time periods, the method of plt collection and the storage media influence post-transfusion plt viability. [5][6][7] The hard-spinning of the plts against a red cell layer in the BC method versus against the bottom of the bag in the PRP method, requiring resuspension of the plts, may induce a collection injury that could potentially compromise the long-term storage of PRP plts compared with BC plts.…”
Section: Plt Concentrates From Whole Bloodmentioning
confidence: 99%
“…11 There is a substantial increase in costs for singledonor compared with pooled random donor plts. As the quality of apheresis plts is similar to pooled random-donor plt concentrates, 3,4 these two products can be used interchangeably based on availability and cost considerations. 12 …”
Section: Apheresis Pltsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above influence platelet storage stability. While the quality and storage stability of PCs prepared from platelet–rich plasma, BCs and apheresis have been investigated [1, 2, 3, 4], no comparative study on leucodepleted PCs prepared from the above methods has been reported. Moreover, it is difficult to ascertain whether the changes observed during storage are related to the collection, processing, e.g.…”
Section: Introductionmentioning
confidence: 99%